ANALYSIS OF INVESTMENT FOR THE DEVELOPMENT OF THE KARANGAGUNG FISH PORT IN TUBAN REGENCY - Suresta Pradana; Wateno Oetomo; Koespiadi Koespiadi (Transpublika Publisher, 2024)
Karangagung Fishing Port (PPI) in the coastal area of Tuban Regency, Palang District is known as the fisheries base in Tuban Regency, even most of the fish production from the Karangagung PPI fishing port has been marketed to all regions in East Java province. The sustainability of the development of an infrastructure project is very important to consider in the development of infrastructure in the maritime sector, especially the fisheries sector. This research will produce an investment analysis on the development of the Karangagung Fishing Port (PPI) infrastructure project which is expected to increase the productivity of the fisheries sector in the area. The investment analysis method used includes the calculation of Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit Cost Ratio (BCR) with the analysis results of NPV value of 6,648,460,488.00, IRR 6.21% and BCR 1.0178 with an investment period of 25 years. From the results of the investment analysis that has been carried out, the NPV value is positive. then the IRR value or the rate of return on an investment with a value greater than the discount factor plan and the benefit value or BCR is more than 1 and the payback period in year 25 is the same as the investment period of 25 years. So, the feasibility of investment is still said to be feasible to use for handling the work of the Karangagaung Tuban Fishing Port Development.